The effects of cyanobacterial blooms on the immune system of Elliptio complanata in urban and agricultural areas in the Yamaska River watershed - F Gagné; M Gélinas; M Fortier; M Fournier (Invertebrate Survival Journal, 2018)
The cumulative effects of cyanobacterial blooms at sites impacted by urban or agricultural activity, could be detrimental to local freshwater mussels. The purpose of this study was to examine and compare the resulting toxicity using an upstream–downstream approach at four sites in the Yamaska River. Mussels were caged and placed at a site where cyanobacterial blooms were present, a site that receives municipal effluent from a small city of 75,000 inhabitants, and a site that drains a large agricultural area—plus a reference site in Lake Saint-Pierre (Quebec, Canada) for four months spanning the summer and fall (June to October). Effects on immunocompetence were monitored by testing for hemocyte counts, viability, phagocytosis, production of nitric oxide (NO), lysozyme (LY), reactive oxygen species (ROS), thiol contents, and inflammation induced by cyclooxygenase (COX) activity and glutathione S-transferase (GST) activity. Cyanobacterial blooms occurred at the target site only, reaching levels of 2.1 million cyanobacteria/L and 3 g/L of microcystin-LR in surface waters. Although most of the immune parameters were affected at the urban, agricultural and cyanobacteria sites, ROS and LY were the most responsive to cyanobacterial bloom, with a significantly greater response than the agriculture, urban and reference sites. The results also suggest that the effects of cyanobacterial blooms are spatially localized; they are not found at the downstream urban and agriculture sites in the Yamaska River.